Kekerasan dalam Pendidikan Islam: Sebuah Kajian Antropologis-Teoretis - Ridwan, Aulia (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2023)
This article examines the interaction between violence and discipline within Islamic boarding schools (pesantren) through an Islamic educational anthropology approach. The study reveals how social norms and power dynamics in pesantren shape disciplinary practices, which often involve both physical and symbolic violence. By highlighting the importance of values such as compassion and justice in Islamic discipline, the article advocates for educational reform in Islamic institutions to create a safe and supportive environment for students’ rights. This study contributes significantly to Islamic education discourse by introducing a more humanistic, non-violent disciplinary approach. Further research is recommended to explore the application of non-violent Islamic disciplinary methods and to evaluate the impact of school culture on the potential for violence within Islamic educational institutions